Balancing Risk and Benefit of Antiplatelet Therapy in the Acute Coronary Syndrome Patient with Thrombocytopenia: A Case Report - Hendrijanto, Johanes David; Susila, I Ketut; Putra, Ngurah Agung Reza Satria Nugraha (Cardiovascular and Cardiometabolic Journal (CCJ), 2025)
Background: Antiplatelets are one of the cornerstones of treatment for Acute coronary syndrome (ACS), although it is risky in patients with thrombocytopenia. In choosing antiplatelets, physicians must carefully weigh the risks of ischemia and bleeding. Case Summary: A 68-year-old male came to ED with a 2-day history of left-sided chest pain, exacerbated 1 hour before admission. The preliminary ECG revealed ST elevation in lead V2-V5 and laboratory examination showed low platelets in four days (32x103/uL; 29x103/uL; 47x103/uL; 87x103/uL). The patient received a loading dose of Aspirin 160 mg. However, Clopidogrel 1x75mg was administered on the second day of treatment. After 5 days of treatment, the patient's condition improved, and his platelet count increased steadily. Conclusion: Antiplatelet therapy is required to avoid ischemic complications, but it enhances the risk of bleeding in individuals with thrombocytopenia. There have been few studies on the use of antiplatelets in thrombocytopenia. Monotherapy is preferred over dual therapy, however the risk/benefit ratio, clinical response, and monitoring for bleeding issues in the patient must all be considered. -- Highlights: 1. This case illustrates that cautious antiplatelet monotherapy may be a viable strategy in ACS patients with thrombocytopenia. In this 68-year-old with ST-elevation MI and platelets <50×10³/μL, delayed Clopidogrel monotherapy—guided by clinical stability and rising platelet counts—led to improvement without bleeding complications.